-Implementation and preparation of the planning budget in civil societyorganizations in Turkey. “Which concerns Syrian refugees"- A field study - Kurdieh, Ramya (Journal of Economic, Administrative and Legal Sciences, 2017)
This paper examined the extent of the preparation and implementation of planning budgets in foreign civil Society organization (FCSO) in Turkey interested Syrian affairs, that aim analyze and evaluate the factual preparation and implementation of planning budgets by these organizations, identifying key problems encountered during the implementation stage by f organizations, to achieve the study objectives, the researcher has developed and distributed a questionnaire that was completed by 70 (FCSO) in Turkey. The study concluded that: the most of the (FCSOs) in Turkey is applying planning budgets, and rely on scientific principles, but the budget numbers are not convincing for those in charge of implementation. CSOs that apply planning budgets encounter problems such as: - lack of qualified personnel to oversee budget preparation and implementation. - The technical and behavioral problems that arise in preparing and implementing the budget. The organizations that rely on scientific methods when preparing and implementing planning budgets and working to reach a complete and coherent budget, can be to rely on it. It also can be modified planning budget numbers easily according to the change in the internal and external conditions of the organization while maintaining its validity as a basis for planning and control. * (FCSOs) in Turkey are setting budgets for short periods often years and is split these periods to control periods where they are at the end of the period to identify and analyze the differences between what is planned and what is real, which will accelerate in the early and treatable detect deviations. The study reveals a set of recommendations in that CSO should solve problems that affect the application of the planning budgets through concerned staff training, and CSO should employ recent scientific approaches for estimating their budgets in order to produce actual and achievable projections